2015
DOI: 10.1103/physreva.91.023807
|View full text |Cite|
|
Sign up to set email alerts
|

Speckle fluctuations resolve the interdistance between incoherent point sources in complex media

Abstract: We study the fluctuations of the light emitted by two identical incoherent point sources in a disordered environment. The intensity-intensity correlation function and the speckle contrast, obtained after proper temporal and configurational averaging, encode the relative distance between the two sources. This suggests the intriguing possibility that intensity measurements at only one point in a speckle pattern produced by two incoherent sources can provide information about the relative distance between the sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As laid out in a review by Berkovits and Feng (Berkovits and Feng, 1994) the above concepts on the correlation functions can be conveniently extended to describe also correlations in frequency as well as in the angle or in the spatial position of the emission from the disordered medium. Note also the possibility offered in optics to probe other quantities, such as the (0) correlations (Cazé et al, 2010;Shapiro, 1999), that arise when the source is embedded inside the scattering medium, a setup that could be used for imaging purposes (Carminati et al, 2015;Skipetrov and Maynard, 2000).…”
Section: B Conductance Fluctuationsmentioning
confidence: 99%
“…As laid out in a review by Berkovits and Feng (Berkovits and Feng, 1994) the above concepts on the correlation functions can be conveniently extended to describe also correlations in frequency as well as in the angle or in the spatial position of the emission from the disordered medium. Note also the possibility offered in optics to probe other quantities, such as the (0) correlations (Cazé et al, 2010;Shapiro, 1999), that arise when the source is embedded inside the scattering medium, a setup that could be used for imaging purposes (Carminati et al, 2015;Skipetrov and Maynard, 2000).…”
Section: B Conductance Fluctuationsmentioning
confidence: 99%
“…This situation is different from that analyzed in Refs. [19,20,25], where spontaneous emission by two independent sources (e.g., two fluorescent molecules) in a structured environment was considered. In this case, it was shown that intensity fluctuations are influenced by a cross term involving the CDOS.…”
Section: Extended Sources In Photonic Cavitiesmentioning
confidence: 99%
“…The study of field correlations in speckle patterns produced by three-dimensional disordered materials has recently evolved towards the quest for non-universal properties, which could be connected with the morphology of the medium at sub-λ scale [3]. It has been recently shown that the degree of mutual polarization for different points in speckle patterns depends on the scattering sample [4], while spatial field correlations can reveal the relevant length scales of the medium morphology [5] or the distance between point sources embedded in the sample [6]. In particular the speckle pattern in the near field of a scattering medium shows sub-λ grain size which can be correlated with the sub-λ structure of the medium.…”
Section: Introductionmentioning
confidence: 99%